Clinical cardiac electrophysiology : techniques and interpretations - Josephson, Mark E (Lea and Febiger, 1993)
The purpose of this book is to provide the internist and clinical cardiologist with the means to understand the capabilities and limitations of clinical cardiac electrophysiologic techniques so as to enable them to select patients who will benefit from such studies. Secondly, this book provides the information which is essential to understand the technical aspects of performing electro-physiologic studies in order to perform safe and reproducable studies which can be based. The methods of analyzing the host of brady-tachy-arrhythmias from both diagnostic and therapeutic standpoints are detailed. In addition, the role of the electrophysiology laboratory as a therapeutic tool in the form of catheter ablation is also discussed.
Keywords: Heart; angiologie; radiologie, nukleární medicína a zobrazovací metody; elektrodiagnostika; Electrophysiology; srdce; Ablation Techniques; fyzika, biofyzika; Arrhythmias, Cardiac; Electrocardiography; elektrokardiografie; chirurgie; Electrodiagnosis; fyziologie; kardiologie; elektrofyziologie; ablace; patologie; srdeční arytmie